The Analysis of Factors Affecting Work Performance of Employees (Case Study at The Production Department of PT Yahata Fastener Indonesia) - Dinar Nur Affini; Arwi Farida; Unang Toto Handiman; Ahmad Hidayat Sutawidjaya (Jurnal Ilmiah Manajemen dan Bisnis, 2022)
This study aims to analyze the factors that affect employees' work performance in the production department of PT. Yahata Fastener Indonesia. The population in this study were all employees of the production department of PT. Yahata Fastener Indonesia. The sample used is a saturated sample that is as many as 50 respondents using. Methods of data collection using survey methods, with the research instrument is a questionnaire. Data analysis this study uses SPSS 22. The result of this study is that job training has a positive and significant effect on employees' work performance in the production department of PT. Yahata Fastener Indonesia. In addition, the physical and work environment has a positive and significant impact on the employees' work performance of the production department of PT. Yahata Fastener Indonesia. Finally, financial compensation has a positive and significant effect on employees' work performnace in the production department of PT. Yahata Fastener Indonesia.